The Early Identification of Children with Disabilities in Public Schools in Muscat Governorate, Sultanate of Oman - ALZADJALI, Zubaida Ali Abdullah; Badzis, Mastura (IIUM Journal of Educational Studies, 2025)
This study focuses on evaluating the current state of early identification programs for children with disabilities in public schools in Muscat Governorate, Sultanate of Oman, and analyzing their effectiveness in detecting disabilities and providing appropriate interventions. The importance of this study stems from the critical role such programs play in improving the quality of life for children with disabilities and enhancing their opportunities for familial, social, and educational inclusion. Education in Oman is a national priority, and public education covers all segments of society, including students with disabilities, for whom inclusive classroom programs have been implemented in public schools. These inclusive classrooms represent an educational model aimed at integrating students with hearing, intellectual disabilities, or learning difficulties into the general educational environment while providing the necessary support to ensure their active participation, as part of Oman’s commitment to equal opportunities and inclusive education. The study adopted a descriptive analytical approach by developing a questionnaire consisting of ten main axes derived from relevant literature and international standards. It was applied to a stratified random sample of 186 employees across 15 early intervention centers in Muscat Governorate. The findings were supported by semi structured interviews and data analysis conducted using Smart PLS software, employing Confirmatory Factor Analysis (CFA). The results revealed significant gaps in the quality of services provided, most notably the lack of coordination among relevant entities, deficiencies in the training and qualification of professional staff, and low parental awareness regarding the importance of early identification. The study also highlighted the need to develop institutional policies and infrastructure in line with global standards, with a particular emphasis on activating the family’s role in all stages of assessment and intervention. The research concluded with a set of recommendations aimed at improving service quality, enhancing institutional integration, and developing more effective and sustainable assessment mechanisms, contributing to a qualitative advancement in the field of early identification of children with disabilities in Oman.